Covid-19 Impact on Agricultural Farmer's Social, Physical, and Mental Health: A Literature Review - Sulistyono, R Endro; Hayati, Nurul (Universitas Airlangga, 2021)
Background: COVID-19 pandemic disrupted in many business sectors and affected negatively the agricultural sector. The objectives of this review are to determine the impact of COVID-19 in the social life, physical and mental of agricultural farmer.Method: This study was a literature review. The population in the study was farmers. The process of review was; identification of literature; screening questions; eligibility using inclusion criteria; and assessment of the quality of the studies. This review was conducted by identify relevant literature, in Science Direct, PubMed, Scopus and Google Scholar using the following keywords: